2019
DOI: 10.1177/1060028019835202
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Anti–Factor Xa and Activated Partial Thromboplastin Levels for Monitoring Unfractionated Heparin

Abstract: Background: Lab tests such as activated partial thromboplastin time (aPTT) or anti–factor Xa (anti-Xa) levels are typically used to monitor intravenous unfractionated heparin (IV heparin), with recent evidence suggesting that anti-Xa levels may provide a more accurate measure of anticoagulation. Objective: The Lexington Veterans Affairs Health Care System transitioned from using aPTT to anti-Xa levels in January 2017. This study was conducted to evaluate the efficacy and safety of this change. Methods: This wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Despite the growing use of anti-FXa assay, UFH therapy has been widely monitored by the aPTT assay because of its simplicity, lower cost, and widespread availability. [4][5][6][7] Nevertheless, the aPTT assay can be affected by various pre-analytical and analytical factors. [8][9][10][11][12][13] Several studies have reported the discordance of the results obtained from the aPTT and anti-FXa assays for UFH monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the growing use of anti-FXa assay, UFH therapy has been widely monitored by the aPTT assay because of its simplicity, lower cost, and widespread availability. [4][5][6][7] Nevertheless, the aPTT assay can be affected by various pre-analytical and analytical factors. [8][9][10][11][12][13] Several studies have reported the discordance of the results obtained from the aPTT and anti-FXa assays for UFH monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Several studies have reported the discordance of the results obtained from the aPTT and anti-FXa assays for UFH monitoring. 6,7,12,13,15,16 In addition, the UFH-induced prolongation of aPTT is highly dependent on the reagent and analyzer used. In this study, we aimed to determine the optimal thrombin concentration used in the hcTT assay and establish the potential of using the assay for UFH monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, each institution has its own protocol for providing optimal unfractionated heparin therapy to achieve the target activated partial thromboplastin time (APTT) or activated clotting time (ACT) when patients are receiving extracorporeal membrane oxygenation (ECMO). Although studies have shown that unfractionated heparin therapy is more strongly associated with anti-Xa activity, measurement of anti-Xa activity as a routine practice is not necessarily the standard of care due to lack of evidence 1 4 .…”
Section: Introductionmentioning
confidence: 99%